2022-RA-997-ESGO Lung recurrence of endometrial adenocarcinoma: impact of molecular profile and role of local therapies on prognosis. (20th October 2022) - Luzarraga, Ana; Bebia, Vicente; Lopez-Gil, Carlos; Montoya, Maria Pilar; Giraldo, Alexandra; Jauregui, Alberto; Verges, Ramona; Castellvi, Josep; Garcia-Jimenez, Angel; Colas, Eva; Gil, Antonio; Cabrera, Silvia
Abstract : Introduction/Background: Endometrial cancer(EC) lung recurrence can be classified as multiple-site recurrence (affecting the lung and other organs) or isolated lung recurrence (affecting only the lung). Isolated lung recurrent patients may have the potential for long-term disease control and improved prognosis with local treatments: stereotactic body radiation therapy (SBRT) or metastasectomy. Methodology: This is a retrospective single-center study including consecutive women diagnosed with stage I-IVA EC at the Hospital Vall d'Hebron between 1995 and 2021 with first recurrence affecting the lung. Patients were classified as multiple-site metastatic or isolated lung recurrence, and these last according to the treatment received (local or systemic). We aimed to analyze local response rate and prognostic outcomes according to received treatment and the molecular classification (MC). Results: Isolated lung systemic-treated patients (n=15) were older (77 vs 69.7 years-old at relapse, p=0.43) and had more often bilateral (73.3%vs37.5%, p=0.008) and a higher number of metastases (p=0, 001) than locally-treated patients (n=16). Of the locally-treated group, 5 were treated with SBRT and 11 with surgery. Complete response was achieved in 80% and 90.9%, respectively. 9(56%) vs 1(11, 1%) patients were alive and without disease at the end of follow-up (median follow-up: 5.9 years) in local and systemic treatment groups, respectively(p=0, 05)(Image2). Median-time-to-progression was higher in local-treatment group (3, 5 ys vs 0, 7 ys, p=0.029), as well as 5-year-OS (80, 8% vs 44, 4%, p=0.88). No statistically significant differences were found between multiple-site metastasic patients and isolated lung recurrent patients regarding molecular profiling:21.9% were MSI, 34.4% NSMP, 21.9% p53-abn and 0% POLEmut(p=0, 537). Disease-free-survival (DFS) by molecular classification was similar between isolated lung recurrent patients after their treatment ( figure 1 ). Conclusion: Isolated lung recurrent patients locally-treated had the best DFS, OS, and a higher median-time-to-progression. Among tumors recurring in the lung, NSMP was the most frequent group. DFS was similar after lung recurrence treatment regarding molecular profile in the oligometastatic cohort.